2003
DOI: 10.1002/vnl.10074
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of organotin stabilization of poly(vinyl chloride). 6. Compatibility of organotin stabilizers with PVC

Abstract: Compatibility of PVC with liquid alkyltin alkylthioglycolate stabilizers was studied by thermal methods, including isothermal calorimetry of mixing, DSC, DMA, and dielectric relaxation. The enthalpy of mixing of PVC with the series of alkyltin alkyl thioglycolates was measured over the entire concentration range at ambient conditions. It was found that all tested compounds are compatible with PVC in a broad concentration range and form homogeneous mixtures. The results are discussed in terms of the superpositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Gupta 61 gave details of the conditions of sample preparation; e.g., dispersion of the stabilizer in PVC resin, concluding that the degree of dispersibility was determined by physical properties of the stabilizer and, in turn, affected the stabilizing efficiency of the composition. 233 It was found that all tested compounds are compatible with PVC in a broad concentration range. Brecker 211 stressed the importance of dialkyltin bis(isooctyl mercaptoacetate) because of the socalled resin plasticizing effect manifested by lower melt viscosity and the need to adjust lubrication when the stabilizer is changed.…”
Section: Mechanisms Of Actionmentioning
confidence: 91%
See 3 more Smart Citations
“…Gupta 61 gave details of the conditions of sample preparation; e.g., dispersion of the stabilizer in PVC resin, concluding that the degree of dispersibility was determined by physical properties of the stabilizer and, in turn, affected the stabilizing efficiency of the composition. 233 It was found that all tested compounds are compatible with PVC in a broad concentration range. Brecker 211 stressed the importance of dialkyltin bis(isooctyl mercaptoacetate) because of the socalled resin plasticizing effect manifested by lower melt viscosity and the need to adjust lubrication when the stabilizer is changed.…”
Section: Mechanisms Of Actionmentioning
confidence: 91%
“…Szabo, 232 discussing the properties of dibutyltin bis(isooctyl thioglycollate), pointed out that it is an efficient stabilizer because of its compatibility with polymer. 233 Tin stabilizers were found to form homogeneous mixtures with PVC. Safronov et al 233 published results of physical studies of compatibility of PVC and tin stabilizers.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to reduce this disadvantage some additives are applied to retard both thermal and photodegradation of PVC polymer, namely thermal and photostabilizers. Basic salts [14], soaps [15] and some organic stabilizers [16] are used as thermal stabilizers. Toxicity, environmental pollution and high cost of these additives have imposed a limitation on their use.…”
Section: Introductionmentioning
confidence: 99%